Information System Records of Nutritional Status of Stunted Children Aged Under Five: A Literature Review of Stunting Management in Pandemic Era - Nopi Nur Khasanah; Yeni Rustina; Dyah Wiji Puspita Sari; Apriliani Yulianti Wuriningsih (Amerta Nutrition, 2022)
Background: Policies and regulations related to stunting reduction in Indonesia are manifested in both specific and sensitive interventions. Throughout the process, these intervention efforts require cross-sector cooperation while noting that stunting is caused by multi-dimensional factors. Unfortunately, the current Covid-19 pandemic has worsened the target achievement of stunting reduction due to limited human resources at the primary service level and various Covid-19 prevention protocols that must be adhered to; both are considered as factors leading to the declining of services at the community level.   Objectives: This research was conducted to analyze the implementation of stunting prevention policy by reviewing the literature that doing a research to prevent stunting in pandemic era. Discusion: The results showed that the lack of human resources, which results in inadequate health services, may be one of the indirect causes of ineffective of stunting prevention policy. Conclusions: The development of an information system for recording the nutritional status of children under five with stunting can be an alternative to prevent the impact of stunting through a multilevel approach by involving health cadres and health professionals who are responsible for public health within the community health center scope.